2014
DOI: 10.1002/ece3.1165
|View full text |Cite
|
Sign up to set email alerts
|

Can patterns of chromosome inversions in Drosophila pseudoobscura predict polyandry across a geographical cline?

Abstract: Female multiple mating, known as polyandry, is ubiquitous and occurs in a wide variety of taxa. Polyandry varies greatly from species in which females mate with one or two males in their lifetime to species in which females may mate with several different males on the same day. As multiple mating by females is associated with costs, numerous hypotheses attempt to explain this phenomenon. One hypothesis not extensively explored is the possibility that polyandrous behavior is captured and “fixed” in populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 91 publications
(147 reference statements)
3
15
0
Order By: Relevance
“…One possibility is that the unique system of third chromosome inversions in this species has influenced the genetic diversity available within populations that enables them to respond effectively to environmental conditions [ 34 ]. In our populations, individuals heterozygous for inversion sequences are more common in our northern laboratory populations, which may have preserved small body sizes in this population [ 35 ]. However, we note that the closely related D. subobscura also has chromosome inversions and yet shows the more common pattern of larger body sizes at lower temperatures due to selection for efficient wing loading at different body sizes [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the unique system of third chromosome inversions in this species has influenced the genetic diversity available within populations that enables them to respond effectively to environmental conditions [ 34 ]. In our populations, individuals heterozygous for inversion sequences are more common in our northern laboratory populations, which may have preserved small body sizes in this population [ 35 ]. However, we note that the closely related D. subobscura also has chromosome inversions and yet shows the more common pattern of larger body sizes at lower temperatures due to selection for efficient wing loading at different body sizes [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most enduring and widespread temperature-derived patterns in nature are latitudinal clines with distinctive equator pole patterns observed for traits such as adult body size, juvenile development time, desiccation resistance, and cold tolerance ( Atkinson and Sibly 1997 ; Gilchrist et al 2004 ; Kellermann et al 2009 ; Kingsolver 2009 ). There are also reports of a latitudinal cline in polyandry in 2 North American Drosophila species, with northern populations showing higher frequency of polyandry ( Pinzone and Dyer 2013 ; Price et al 2014 ). In both species, it is not known whether the clines in polyandry have been shaped and are maintained directly either by environmental temperature or by unique genetic factors.…”
Section: Introductionmentioning
confidence: 98%
“…Polyandry, or mating with multiple males by females, is a widespread behavior, occurring in a diverse array of taxa from a variety of ecological and environmental habitats ( Andersson 1994 ; Birkhead and Møller 1998 ; Taylor et al 2014 ). However, within polyandrous species, there remains considerable variation in the proportion of females routinely mating with multiple males, from as few as 10% to over 90% ( Wedell 2005 ; Taylor et al 2014 ). Females who mate multiply may be advantaged over singly mating females in numerous aspects of their reproductive biology ( Arnqvist and Nilsson 2000 ; Jennions and Petrie 2000 ; Simmons 2001 , 2003 , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prout and Bundgaard 50 provide evidence that suggests genes have a direct influence on postmating responses, but this is not the case always as many studies found no relation between chromosomal arrangements and remating rate (Table 1). 51 During mating, molecular contribution of males as well as females is required. Males provide sperm as well as seminal proteins to the female.…”
mentioning
confidence: 99%